Factors affecting employee engagement among academic staff’s Academy Contemporary Islamic Studies, UiTM Shah Alam / Jamalinah Yahya - Yahya, Jamalinah (Faculty of Business and Management, 2020)
The purpose of this study is to examine the factors affecting employee engagement among academic staff. This study involved academic staff from Academy Contemporary Islamic Studies, UiTM Shah Alam as respondents for this study. This research is a quantitative research which used the self-administered questionnaires as instruments to collect the data. The sampling technique that been used in this study is the census method and the questionnaires had been distributed to 104 respondents with 78.84 percent of the response rate. The data collected is then evaluated by using Statistical Package for Social Science (SPSS). Descriptive analysis, reliability analysis, Pearson’s correlation analysis, and multiple regression analysis were used in this study to identify the relationships between work-life balance, career development, leadership and employee engagement. The findings of the study showed that there is a significant relationship between work-life balance and career development with employee engagement. However, there is no significant relationship between leadership and employee engagement.